Fiscal federalism - Oates, Wallace E. (New York : Harcourt Brace Jovanovich, 1972)
The book attempts to first set forth the economic theory of public finance under a federal system of government.
Includes bibliographical references and index.
osc 30/06/2017
Loans
Keywords: Intergovernmental fiscal relations; Grants-in-aid.; Finance, Public